A hyper-connected but less efficient small-world network in the substance-dependent brain. (1st July 2015) - Wang, Ze; Suh, Jesse; Li, Zhengjun; Li, Yin; Franklin, Teresa; O'Brien, Charles; Childress, Anna Rose
Highlights: Functional connectome was assessed in drug addiction. Drug addicts showed hyper-connection. Drug addicts had lower connectome communication efficiency Drug addicts had reduced small-worldness. Abstract: Background: The functional interconnections of the addicted brain may differ from the non-addicted population in important ways, but prioranalytic approaches were usually limited to the study of connections between a few number of selected brain regions. Recent approaches enable examination of the vast functional interactions within the entire brain, the functional connectome (FCM). The purpose of this study was to characterize FCM alterations in addiction using resting state functional Magnetic Resonance Imaging (rsfMRI) and to assess their relations to addiction-related symptoms. Methods: rsfMRI data were acquired from 20 chronic polydrug users whose primary diagnosis was cocaine dependence (DRUG) and 19 age-matched non-drug using healthy controls (CTL). FCM was assessed using graph theoretical analysis. Results: Among the assessed 90 brain subdivisions, DRUG showed stronger functional connectivity. After controlling functional connectivity difference and the resultant network density, DRUG showed reduced communication efficiency and reduced small-worldness. Conclusions: The increased connection strength in drug users' brain suggests an elevated dynamic resting state that may enable a rapid, semi-automatic, execution of behaviors directed toward drug-related goals.The reduced FCM communication efficiency and reduced small-worldness suggest a loss of normal inter-regional communications and topology features that makes it difficult to inhibit the drug seeking behavior.